Information theory and genetic code - Tian, Willie Wei Liang. (2010)
The genetic code, which directs the protein biosynthesis, is an information system [1]. Although not all of its details are known at present, its necessary characteristics are clearly visible for the replication, transcription and translation of the genetic message. Numerous researches have been carried out which shows there appears to be an existence of a universal structure or mechanism which allows the enzymes to repair and protect the fidelity of non-replicating DNA and increase the replication accuracy rate. In this project, my objective is to research more in-depth into this particular area to understand more about the DNA information exchanging process in order to find out whether an error correcting code do really exist in DNA and how it actually operates if the existence of this code could be proven. In this report, the author tries to gather the various works of researchers pertaining to this aspect and gives a brief overview of the current situation. In the following 2 chapters, the author briefly summarized the main concepts of information theory and genetic code respectively. In chapter 4, the author describes the different conjectures and hypotheses put forth and discuss whether there‟s enough evidence to support the notion that information and genetic are correlated. Next, the author narrows down to a single issue concerning the topics in search of the existence of the error correcting code in DNA and methods or case studies to prove its existence. Finally, a conclusion is given in chapter 6 which sums up the whole project main concepts and discuss about the future works that could be done.